2011
DOI: 10.1007/s12098-011-0578-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Hospitalized Children with Pandemic H1N1 Influenza 2009 in Pune, India

Abstract: Hypoxia, ARDS and use of corticosteroids in children with ARDS who were mechanically ventilated were the factors associated with increased odds of mortality. Necropsy also suggested bacterial co-infection as a risk factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 11 publications
1
15
2
1
Order By: Relevance
“…Estimates ranged from 0% to 50% (97% of the estimates) for the hospitalization ICU risk. The highest overall estimates were reported in 4 studies from Germany, India, and Iran, with estimates of 53%-96% (16,(18)(19)(20).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Estimates ranged from 0% to 50% (97% of the estimates) for the hospitalization ICU risk. The highest overall estimates were reported in 4 studies from Germany, India, and Iran, with estimates of 53%-96% (16,(18)(19)(20).…”
Section: Resultsmentioning
confidence: 91%
“…The highest overall HFR estimate (52%) was found in a study conducted at a referral hospital in India (15). When estimates were stratified by age, the highest HFRs for children, adults, and the elderly were 16%, 68%, and 33% respectively, all in India (15)(16)(17).…”
Section: Resultsmentioning
confidence: 95%
“…In another pediatric study in India, Kinikar et al reported that 18% of patients hospitalized with confirmed influenza A (H1N1) virus developed ARDS (24). In this study, 9 of the 15 children who died were found to have histologic pulmonary findings reflective of ARDS at autopsy.…”
Section: Epidemiology Of Rsv and Influenza-induced Ardsmentioning
confidence: 99%
“…Perhaps the most widely used, oseltamivir results in a significant decrease in duration of symptoms as well as severity of illness with early treatment (<48 h of symptoms) (142). Use of oseltamivir in severe cases of influenza A (H1N1) has become standard practice (24, 143), although some studies have shown increased resistance (144). Randolph et al conducted a retrospective study of 838 children admitted to the PICU with confirmed influenza A (H1N1) infection (145).…”
Section: Treatment Options Available For Rsv and Influenza A (H1n1) Vmentioning
confidence: 99%
“…Of the 2,321 references screened, 23 studies were included in the final analysis ( Figure 1). Fourteen studies were case-control studies [15,[31][32][33][34][35][36][37][38][39][40][41][42][43], and nine studies were cohort studies [44][45][46][47][48][49][50][51][52]. In total, 6,105 subjects were analyzed, with 4,700 subjects in case-control studies and 1,405 subjects in cohort studies.…”
Section: Study Characteristicsmentioning
confidence: 99%